European Monitoring Centre for Drugs and Drug Addiction has a vital role in the UK’s ability to respond to illicit drugs and organised crime - Roman-Urrestarazu, Andres; Robertson, Roy; Yang, Justin; McCallum, Alison; Gray, Christina; McKee, Martin; Middleton, John (BMJ (Online), 2018)
By adopting certain “red lines,” including oversight by the Court of Justice of the European Union, the UK will exclude itself from full membership.34 The EMCDDA has provided the EU and its member states with accurate and timely intelligence and evidence based overviews of the European drug landscape that support Europe-wide drug policies,5 as well as facilitating exchange of best practice and identifying priorities for research. The UK also risks exclusion from the EU Drugs Action Plan, an initiative that will strengthen surveillance in three domains: drug markets, drug related crime, and drug supply reduction.9 Finally, the UK will suffer from any barriers to communicating with the EMCDDA and Europol on strategic analysis of drug markets,3 which are founded on the EMCDDA’s datasets and Europol’s intelligence on organised crime.10 Until the UK government can decide on a workable basis for its long term relations with the EU, we cannot know how any future arrangements with the EMCDDA might work. The EMCDDA has had an important, if understated, role in supporting drug and health policy in EU member states, including the UK.